2020
DOI: 10.1038/s41477-020-00764-2
|View full text |Cite
|
Sign up to set email alerts
|

mRNA localization, reaction centre biogenesis and thylakoid membrane targeting in cyanobacteria

Abstract: The thylakoid membranes of cyanobacteria form a complex intracellular membrane system with a distinctive proteome. The sites of biogenesis of thylakoid proteins remain uncertain, as do the signals that direct thylakoid membrane-integral proteins to the thylakoids rather than to the plasma membrane. Here, we address these questions by using Fluorescent in situ Hybridisation to probe the subcellular location of mRNA molecules encoding core subunits of the photosystems in two cyanobacterial species. These mRNAs c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
74
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 50 publications
(80 citation statements)
references
References 62 publications
(115 reference statements)
5
74
0
1
Order By: Relevance
“…4 c, 4d ), our results indicate that the initial steps of RC47 assembly occur predominantly in these newly generated thylakoid fragments. In a very recent study, we have revealed that the mRNA molecules encoding the core subunits of PSI and PSII clustered at the thylakoid surfaces that are mainly adjacent to the central cytoplasm 66 . We showed that the locations of mRNA molecules correspond to the sites of translation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 c, 4d ), our results indicate that the initial steps of RC47 assembly occur predominantly in these newly generated thylakoid fragments. In a very recent study, we have revealed that the mRNA molecules encoding the core subunits of PSI and PSII clustered at the thylakoid surfaces that are mainly adjacent to the central cytoplasm 66 . We showed that the locations of mRNA molecules correspond to the sites of translation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the orders of assembly of photosynthetic complexes, our study also provides clues about the de novo membrane integration and assembly sites of photosynthetic complexes and the dynamics of their subcellular locations. The thylakoid membranes 63 , thylapse membrane domains 15 or PratA-defined membrane (PDM) regions 56,[64][65][66] in Synechocystis, and the translation zones in the chloroplast of Chlamydomonas 67,68 have been proposed to be the principal sites for the initial biogenesis and/or assembly of photosynthetic complexes, in particular PSII. Our confocal images showed explicitly that during the initial stages of thylakoid biogenesis, compared to other photosynthetic complexes, PSII complexes exhibited a greater accumulation on one longitudinal side of the Synechoccoccus cell, where the newly synthesized thylakoid fragments appear (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the assembly orders of photosynthetic complexes, our study also provides clues about the de novo membrane integration and assembly sites of photosynthetic complexes and the dynamics of their subcellular locations. The thylakoid membranes 63 , thylapse membrane domains 15 or PratA-defined membrane (PDM) regions 56,[64][65][66] in Synechocystis, and the translation zones in the chloroplast of Chlamydomonas 67,68 have been proposed to be the principal sites for the initial biogenesis and/or assembly of photosynthetic complexes, in particular PSII. Our confocal images showed explicitly that at the initial step of thylakoid biogenesis, compared to other photosynthetic complexes, PSII complexes exhibited a greater accumulation on one longitudinal side of the Synechoccoccus cell where the newly synthesized thylakoid fragments appear (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Functionally, the prime targets of CrhR interaction were consistently observed to include transcripts associated with photosynthesis, light harvesting or directly encoding core photosystem proteins ( Table 1 ). A role in the biology of photosynthesis-relevant mRNAs would further be consistent with the demonstrated localization of ribosome-associated CrhR at the thylakoid membrane (Rosana et al ., 2016) and also the observation that psbA and psaA mRNAs are transported to the thylakoid membrane and possibly translated by thylakoid-associated ribosomes (Tyystjärvi et al ., 2001; Mahbub et al ., 2020). These findings point to a possible involvement of CrhR in physiological secondary structure rearrangements of the identified mRNAs that could influence translation on thylakoid membrane associated ribosomes.…”
Section: Discussionmentioning
confidence: 99%